VD_FINDINFO AI 522/09 - 488/2011 vom 29. Oktober 2011 - VD Tribunal cantonal (2011)
RENTE D'INVALIDITÉ, RÉVISIONPRESTATION D'ASSURANCE, AFFECTION PSYCHIQUE | 28 al. 2 LAI, 4 al. 1 LAI, 17 al. 1 LPGA, 8 al. 1 LPGA